(untitled) (Journal of Social Sciences Review, 2023)
Allah has made the religion of Islam a means of guidance and salvation for all mankind until the Day of Judgment. Now, until the Day of Judgment, no prophet will come, nor will any revelation be revealed, but the guidance, welfare, and salvation of the human race until the Day of Judgment. It depends on the Holy Qur’an and the teachings of the Holy Prophet. But here, the question arises that with the passage of time, changes in society and society keep happening because changes in the conditions of the world are an essential part of human life. In the Qur’an and Sunnah, there is no partial solution to all the problems until the Day of Resurrection, and there cannot be, but the principles of all the problems and orders are there. Therefore, Islam has given human society the authority to make decisions in the light of the Qur’an and Sunnah in accordance with the circumstances and occasions in the light of the principles of the Qur’an and the Sunnah. Therefore, the necessity and importance of Ijtihad cannot be denied with the change of circumstances, and also, Ijtihad is the Jugular Vein of Muslim Ummah. In this paper, considering the social changes, the need for ijtihad will be commented on in light of the sayings of scholars.